Socioenvironmental and Spatial Criteria as Tools for the Management and Conservation of Hydrozoans in Protected and Unprotected Areas - Mariae C. Estrada-González; María Esther Jiménez-López; Leonardo Huato-Soberanis; María A. Mendoza-Becerril (Diversity, 2023)
The cnidarians of the class Hydrozoa comprise 3720 species, are globally distributed, and can have complex life cycles. In the Espíritu Santo Archipelago (ESA), Mexico, hydrozoans are understudied, and, for this reason, the present work describes the taxocene of hydrozoans and their oceanographic preferences in the area. Hydrozoans were collected at 12 sampling stations in the archipelago during the temperate season; these organisms were morphologically identified and a systematic list including socioenvironmental attributes (SEA) was created. Species richness was used to assess the representativeness of the sampling and identify the distribution of species assemblages in relation to their SEA and environmental factors. In total, 31 species were described, representing 70% of the area’s potential diversity, and 97% of observations described species that had not yet been recorded in the area. Native, cryptogenic, and exotic species were found, including stinging and harvestable species. Groups with low, medium and high species richness were distributed heterogeneously, forming a spatial aggregation pattern. The results of this work suggest that the ESA has a highly diverse taxocene, with SEA and spatial aggregate structure relevant for integrative management and conservation of hydrozoans in natural protected areas.